2019
DOI: 10.1101/714477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic properties of structural variants and short tandem repeats that impact gene expression and complex traits in humans

Abstract: S t r u c t

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(30 reference statements)
3
3
0
Order By: Relevance
“…For structural variants (SVs), a 9-fold increase in rare (study MAF 0<=MAF<1%) duplications, and 18fold increase in rare multi-allelic copy number variants (mCNVs), was observed in overexpression outliers compared with non-outliers ( Fig 2B) ( Table S8). The findings for SVs agrees with recent consortium findings detailed previously 20 .…”
Section: Mapping Large-effect Rare Variants Impacting Gene Expressionsupporting
confidence: 92%
“…For structural variants (SVs), a 9-fold increase in rare (study MAF 0<=MAF<1%) duplications, and 18fold increase in rare multi-allelic copy number variants (mCNVs), was observed in overexpression outliers compared with non-outliers ( Fig 2B) ( Table S8). The findings for SVs agrees with recent consortium findings detailed previously 20 .…”
Section: Mapping Large-effect Rare Variants Impacting Gene Expressionsupporting
confidence: 92%
“…This was true across variant classes in both studies, with the exception of duplications in 1KGP, which were less correlated (r=0.74), likely as a result of limited genotyping sensitivity in 1KGP due to the use of low coverage WGS data ( Figure S15,S16). These results support that the i2QTL SV call set is accurate and contains most common SVs discoverable using short read sequencing data as well as novel, rare SVs, making it a valuable resource for examining functional differences between the SV classes (Jakubosky et al, 2019).…”
Section: Comparison Between Svs In I2qtl Gtex and 1kgpsupporting
confidence: 70%
“…Overall, this study provides a roadmap for discovering and genotyping SVs from WGS data and establishes a high-quality catalog of SVs and STRs that can be used in future genotyping efforts. A companion paper (Jakubosky et al, 2019)examines how the i2QTL SVs and STRs characterized here influence gene expression and contribute to disease risk. These studies demonstrate that SVs and STrs can be reliably identified and genotyped for hundreds of samples and used to study the impact of this class of genetic variation on human health.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To address this gap, we developed a comprehensive map of regulatory variation in the MHC region using deep WGS from 419 individuals and RNA-seq data from matched iPSCs. We have previously shown that iPSCs are well-powered for eQTL mapping (Bonder et al, 2019; Jakubosky et al, 2019a; Jakubosky et al, 2019b), have a distinct regulatory landscape relative to somatic tissues (DeBoever et al, 2017), and thereby provide insights into regulatory variants that exert their effects during early development. While we demonstrate the feasibility of generating a map of regulatory variation for the MHC region and its utility for examining molecular mechanisms underlying disease associations in the interval, future studies using eQTLs from other cell types could increase the number of complex trait loci in the interval that are functionally annotated.…”
Section: Discussionmentioning
confidence: 99%